STUDENTS’ PERCEPTIONS OF E-LEARNING FOR ESL/EFL IN SAUDI UNIVERSITIES AT TIME OF CORONAVIRUS: A LITERATURE REVIEW - Khaled Layali; Ahmed Al-Shlowiy (Indonesian EFL Journal, 2020)
Coronavirus (COVID-19) was declared a world pandemic by the World Health Organization (WHO) on January 30, 2020. As a safety measure to protect people, most governments in the world, including Saudi Arabia, decided to close universities and workplaces. Prompted by this shut down, the researchers aimed to review the students’ perceptions of e-learning for ESL/EFL in Saudi universities at this Coronavirus time. As such, this review reported on four primary studies that were found relevant to its focus during the period from January 2020 till April 2020 (Abu-Ayfah, 2020; Ahmad, 2020; Alshehri Cumming, 2020; Hakami, 2020). As a historical perspective of the review’s focus, it also reported on other four primary studies dating back to 2018 and 2019 (Alshehri, Rutter Smith, 2019; Mutambik, 2018; Oyaid Alshaya, 2019; Sharma, 2019). The review’s objectives were to report: 1) students’ perceptions of e-learning for ESL/EFL, 2) benefits of e-learning for ESL/EFL, and 3) drawbacks of e-learning for ESL/EFL in Saudi universities. Moreover, this review was compared to a conference paper from China (He, 2020) as it presented a strategy to continue college English learning and teaching at Coronavirus time. Results showed students’ positive views, many benefits and limited drawbacks of e-learning for ESL/EFL in Saudi universities.Keywords: e-learning; ESL/EFL; students’ perceptions; benefits and drawbacks; Saudi education.